Polymorphism of the Flap Endonuclease 1 Gene in Keratoconus and Fuchs Endothelial Corneal Dystrophy - Wojcik, Katarzyna A. (MDPI, 2014)
Oxidative stress is implicated in the pathogenesis of many diseases, including serious ocular diseases, keratoconus (KC) and Fuchs endothelial corneal dystrophy (FECD). Flap endonuclease 1 (FEN1) plays an important role in the repair of oxidative DNA damage in the base excision repair pathway. We determined the association between two single nucleotide polymorphisms (SNPs), c.–441G>A (rs174538) and g.61564299G>T (rs4246215), in the FEN1 gene and the occurrence of KC and FECD. This study involved 279 patients with KC, 225 patients with FECD and 322 control individuals. Polymerase chain reaction (PCR) and length polymorphism restriction fragment analysis (RFLP) were applied. The T/T genotype of the g.61564299G>T polymorphism was associated with an increased occurrence of KC and FECD. There was no association between the c.–441G>A polymorphism and either disease. However, the GG haplotype of both polymorphisms was observed more frequently and the GT haplotype less frequently in the KC group than the control. The AG haplotype was associated with increased FECD occurrence. Our findings suggest that the g.61564299G>T and c.–441G>A polymorphisms in the FEN1 gene may modulate the risk of keratoconus and Fuchs endothelial corneal dystrophy.